Digital Dramaturgy and Young Women's Personal Branding: A Qualitative Study of @anindythaarsa's TikTok Content - Bilqis Lexaluna Zahra; Zainal Abidin Achmad (Universitas Lambung Mangkurat, 2025)
This study examines the personal branding strategy of Anindytha Arsa (@anindythaarsa) on TikTok, reflecting the growing use of social media for career development and youth empowerment. The research identifies elements of personal branding in her content and explores the meanings behind her messages. Using a qualitative content analysis approach, the study analyzed 20 TikTok videos uploaded between January and October 2024, each exceeding 50,000 views and 500 interactions. The analysis applied Hubert K. Rampersad’s theory of authentic personal branding and Erving Goffman’s dramaturgy. Findings reveal that Anindytha Arsa constructs an image of being independent, educated, religious, and inspirational. Her personal branding is expressed through three aspects: the self-image she highlights, the values she promotes, and her communication style. Consistent content focusing on motivation, collaboration, and women’s empowerment reinforces the impression of authenticity. This research contributes to communication studies by integrating dramaturgy and authentic personal branding theories to explain how TikTok functions as a performative space for authentic self-presentation and empowerment narratives. In conclusion, Anindytha Arsa’s TikTok content functions not only as a means of strengthening her identity but also as a strategic career tool that leverages authenticity and educational value to foster closer engagement with her audience.